Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Political Science; History
Keywords: MALTHUS; T. R.; SMITH; Adam; 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Exchange Rising? Karl Polanyi and Contentious Politics in Contemporary Latin America - Silva, Eduardo (Latin American Politics and Society, 2012)
Free-market reforms in the last quarter of the twentieth century weakened the point of production—labor unions—as the source of effective nonparty political countermovement to liberal capitalism. Has another significant source of societal resistance arisen in association with the resurgence of market economics? Building on the work of Karl Polanyi, this article argues that circuits of exchange—the commodification of labor, land, and money—can be powerful sources of movement against contemporary forms of free-market capitalism. It draws on the cases of Argentina, Bolivia, and Ecuador to explore how Polanyi's exchange-based approach helps to elucidate three phenomena: the great variety of identities behind the myriad movements against free-market capitalism, the emergence of community as a powerful locus for organizing, and the proliferation of new forms of transgressive and highly disruptive direct action to reinforce the debilitated effectiveness of the strike.
Political Science
Keywords: Latin America; circuits of exchange; countermovement

Solidarity Economy in Brazil: Movement, Discourse and Practice Analysis Through a Polanyian Understanding of the Economy - Lemaître, Andreia; Helmsing, A. H. J. (Bert) (Journal of International Development, 2012)
Solidarity economy (SE) initiatives constitute a worldwide phenomenon that is today at the heart of numerous economic and social debates. They are active in very diverse economic sectors, aiming for example to create employment for poor and low-qualified workers. We begin with presenting a Polanyian framework for the analysis of such economic activities, which enables us to develop a plural and integral conception of a productive organisation. We draw on Polanyi's thesis that economy is a political and institutionalised process and present a historic overview of the construction of the SE ‘sector’ in Brazil. We put forward the hypothesis that the SE today in Brazil represents a social movement. Then, we ask ourselves if the SE movement led to a change in grassroots economic initiatives, such as ‘people's cooperatives’. We present the results of exploratory research undertaken on 15 people's cooperatives in the State of Rio de Janeiro and its conclusions. Copyright © 2012 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Brazil; inclusion; international development; local development; people's cooperative; social movement; solidarity economy

The missing movement: a Polanyian analysis of pre‐crisis America - Herman, Dan (International Journal of Social Economics, 2012)
The purpose of this paper is to seek to apply Polanyi's theory of the double movement as a response to the effects of economic liberalization and globalization to the pre‐2007 American economy. In so doing, it seeks to ascertain the reasons why this assumed double movement did not materialize until after the post‐2007 global economic crisis. Design/methodology/approach – This paper is structured as a theoretical and historical analysis, building upon Polanyi's nineteenth century observations and applying them to contemporary policy economic and social experience in the USA in the late twentieth century. The argument proposes a correlation between the missing and/or delayed movement and the role of access to debt and participation in equity markets. Findings – This paper argues that Polanyi's concept of a societal countermovement has been absent from the post‐1970 period of economic liberalism and globalization until just recently due to an explicit attempt by the forces of capital to circumvent its role in lessening the harmful effects of American capitalism. In particular, the double movement that should have sought to lessen income inequality, unemployment and wage stagnation was instead replaced by access to cheap credit and the democratization of market investments that spurred consumer purchases and a false belief that what was good for the markets was good for working class Americans. Research limitations/implications – This paper highlights the need for ongoing research into the sociotropic nature of trade and of economic policy, and its evolution throughout the contemporary period of economic uncertainty and economic transition. Practical implications – The paper proposes several policy implications arising from the contemporary application of Polanyi's double movement, notably related to international trade and public and political support for ongoing trade liberalization. Social implications – This paper highlights important connections in the relationship between economic policy and the day‐to‐day lives of those who are governed by it. Building on “everyday political economy”, it provides a foundation for arguments that a new balance must be found between economic globalization and transnational capital interests and domestic stability. Originality/value – This paper promotes a novel approach to understanding the political economy of pre‐2007 America, in particular the reflexive nature of economic policy and societal perceptions.
Political Science
Keywords: countermovement; double movement; economic liberalization; global economic crisis; globalization

Karl Polanyi: The Limits of the Market - By Gareth Dale - Langton, Robert W. (Political Studies Review, 2012)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Political Science
Keywords: DALE; Gareth; Karl Polanyi: The Limits of the Market (Book); book review; nonfiction

What can Okun teach Polanyi? Efficiency, regulation and equality in the OECD - Hopkin, Jonathan; Blyth, Mark (Review of International Political Economy, 2012)
Arthur Okun famously argued that “effciency is bought at the cost of inequalities in income and wealth”. Okun's trade-off represents the antithesis to Karl Polanyi's view of the relationship that the more embedded markets are in society, the better the social and economic outcomes they produce. This paper refines both these views. We argue that not all forms of market embeddedness are created equal, and that the relationship between equality and efficiency can be both positive and negative. We show this by examining how different ways of embedding economic activity in society through market regulation produce different combinations of efficiency and equality. We identify empirically three broad patterns: market liberal regulatory frameworks that promote competitive markets without decommodifying institutions; embedded liberal regulations that allow markets to work efficiently, but within the framework of decommodification and equality; and embedded illiberalism, where regulations hinder markets in favor of powerful social groups and where decommodification undermines both efficiency and equality. Okun's trade-off emerges as a special case limited to the English-speaking democracies: other OECD countries tend to exhibit either efficiency and equality together, or inefficiency and inequality together. These findings suggest a corrective to both nave market liberal views of the incompatibility of efficiency and equality, but also to the more sophisticated Varieties of Capitalism framework, which pays insufficient attention to the ways in which markets can be embedded in stable but apparently dysfunctional institutional arrangements.
Political Science
Keywords: OECD; OKUN; Arthur; critique; embeddedness; international political economy; regulation

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Sociology; Political Science
Keywords: BLOCK; Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Political Science; Sociology
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Global Climate Governance: A Legitimation Crisis - Van Vossole, Jonas (Review: A Journal of the Fernand Braudel Center, 2012)
This article frames the failure of COP19 in Warsaw, the problems of the RIO+20 summit, the failure of the Copenhagen COP15, and the problems of the carbon markets within a broader legitimacy crisis of global governance, a consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between Marx-type contestation, referring to emerging classes/states, and Polanyi-type contestation, referring to the victims of global mercantilization. As related to climate governance, the roles of the BRICs in climate negotiations and the global environmental justice movement represent these two types of contestation of the established organizational structures within the global capitalist socio-ecology.
Political Science
Keywords: 21st century; BRICS countries - environmental conditions; BRICS countries - politics & government; MARX; Karl; 1818-1883; alienation; capitalism; climate governance; decision making in environmental policy; globalization & politics; history; organizational legitimacy; power (social sciences); research

Embeddedness and regional integration: waiting for Polanyi in a Hayekian setting - Hopner, Martin; Schêfer, Armin (International Organization, 2012)
This article analyzes the social potential of regional integration processes by using the example of European integration. Recent case law from the ECJ has led some observers to argue that judicial decisions increasingly provide European politics with a ôPolanyianö drive. We test this claim by distinguishing three dimensions to European economic and social integration: market-restricting integration, market-enforcing integration, and the creation of a European area of nondiscrimination. We also identify two forms of integration that have different speeds, scopes, and potentials: political integration and judicial integration. The evidence shows that the EU has come closer to Hayek's vision of ôinterstate federalismö than is usually warranted because market-enforcing integration and European nondiscrimination policies have asymmetrically profited from ôintegration through lawö.
Political Science
Keywords: European-integration; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; embeddedness; regional integration; regional-integrationá

Neoliberalism through the Lens of 'Embeddedness' - Paton, Joy (Neoliberalism: Beyond the Free Market, 2012)
Political Science
Keywords: capitalist systems; history of economic thought: individuals; history of economic thought: macroeconomics; political economy

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Economics; Political Science
Keywords: POLANYI; Karl; 1886-1964; free enterprise; neoliberalism; political economy

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
History; Political Science
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Philosophy; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; capitalist systems: planning; coordination; and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; shadow economy